GT algorithm (an enhancement of the group based motion algorithm) - Mark Ben M. Gurduque and Mary Ludeth J. Tabora. 4 0 16; 5 (2003)
u
Undergraduate Thesis: (BS in Computer Studies major in Computer Science) -Pamantasan ng Lungsod ng Maynila, 2003.
Keywords: 2 -- 0; 6; 20; 20; 2